2007
DOI: 10.1007/s00464-007-9494-3
|View full text |Cite
|
Sign up to set email alerts
|

Antireflux surgery for patients with end-stage lung disease before and after lung transplantation

Abstract: The results of this study show that laparoscopic antireflux surgery can be performed safely by an experienced multidisciplinary team for selected patients with ESLD before or after lung transplantation, and that gastric emptying is frequently abnormal and should be objectively measured in ESLD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 16 publications
1
33
0
2
Order By: Relevance
“…Gasper et al showed that 35 operations (15 performed before and 20 after transplantation) were all completed laparoscopically, and 33 (94%) patients recovered uneventfully (one was readmitted for urinary tract infection and one died for causes nonrelated to the transplant). 27 The median hospital length of stay was 2 days. Similarly, Fisichella et al analyzed the perioperative morbidity and mortality of 29 consecutive lung transplant patients and 23 consecutive patients without ESLD (control group).…”
Section: Evidence That Early Antireflux Surgery In Patients With Gerdmentioning
confidence: 99%
“…Gasper et al showed that 35 operations (15 performed before and 20 after transplantation) were all completed laparoscopically, and 33 (94%) patients recovered uneventfully (one was readmitted for urinary tract infection and one died for causes nonrelated to the transplant). 27 The median hospital length of stay was 2 days. Similarly, Fisichella et al analyzed the perioperative morbidity and mortality of 29 consecutive lung transplant patients and 23 consecutive patients without ESLD (control group).…”
Section: Evidence That Early Antireflux Surgery In Patients With Gerdmentioning
confidence: 99%
“…We define a trial of azithromycin as treating continuously with azithromycin for a minimum of Anti-reflux surgery Abnormal GOR (identified by oesophageal pH probe in the majority of studies) is highly prevalent in patients with advanced lung disease and in lung transplant recipients [65,66,68,[121][122][123][124][125][126], and it has been implicated as a risk factor for BOS [65,66,68,127,128]. For this reason, committee members routinely test patients with new onset BOS for GOR.…”
Section: Remarksmentioning
confidence: 99%
“…Антирефлюксное хирургическое лечение. Патологичес кий ГЭР (диагностируемый в большинстве исследова ний с помощью пищеводной зондовой рН метрии) значительно распространен у больных с поздними стадиями легочных заболеваний и у реципиентов после трансплантации легких [65,66,68,[121][122][123][124][125][126].…”
Section: рекомендацияunclassified
“…Антирефлюксное хирургическое лечение (напри мер, фундопликация по Ниссену или Тупе) может быть безопасно выполнено у кандидатов на тран сплантацию с поздними стадиями хронических ле гочных заболеваний или у перенесших трансплан тацию легких с подтвержденным ГЭР [123,124,[127][128][129][132][133][134][135][136][137][138]; тем самым предотвращаются дальнейший рефлюкс и аспирация желудочного со держимого и связанные с ними осложнения.…”
Section: рекомендацияunclassified